고정된 직교격자계를 이용한 파랑 중 전진하는 선박주위 유동의 수치시뮬레이션 - 정광열(Kwang-Leol Jeong); 이영길(Young-Gill Lee) (大韓造船學會 論文集, 2014)
This paper presents a numerical simulation method for the flow around advancing ships in regular waves by using a rectilinear grid system. Because the grid lines do not consist with body surface in the rectilinear grid system, the body geometries are defined by the interaction points of those grid lines and the body surface. For the satisfaction of body boundary conditions, no-slip and divergence free conditions are imposed on the body surface and body boundary cells, respectively. Meanwhile, free surface is defined with the modified marker density method. The pressure on the free surface is determined to make the pressure gradient terms of the governing equations continuous, and the velocity around the free surface is calculated with the pressure on the free surface. To validate the present numerical method, a vortex induced vibration (VIV) phenomenon and flows around an advancing Wigley III ship model in various regular waves are simulated, and the results are compared with existing and corresponding research data. Also, to check the applicability to practical ship model, flows around KRISO Container Ship (KCS) model advancing in calm water are numerically simulated. On the simulations, the trim and the sinkage are set free to compare the running attitude with some other experimental data. Moreover, flows around the KCS model in regular waves are also simulated.